O sinal EMG é um método seguro para avaliar efeitos clínicos sobre a atividade dos músculos mastigatórios, pós reabilitação da DTM? Uma revisão sistemática - Barros, Bruna Massaroto (2021)
Introduction: Different analysis methods have been used to assess temporomandibular disorder (TMD), however, it is still not clear in the literature whether EMG is a safe measure to assess the effects of different clinical interventions as a way to treat this disorder. Objective: To verify through a systematic literature review the EMG signal is a safe method to assess clinical effects on masticatory muscle activity, after TMD rehabilitation. Method: This systematic review was carried out according to the guidelines of the Preferred Items of Systematic Reviews and Meta-Analysis Reports (PRISMA), having as sources, studies that allow a comparative analysis of the EMG activity of masticatory muscles between patients with TMD and postpartum -treatment of healthy individuals, produced between 1990 and 2021, written in English, Portuguese or Spanish and collected in Science Direct, Embase, MEDLINE, PEDro, SciELO, CINAHL and LILACS databases.The terms “temporomandibular disorders” and “electromyography” were verified as Medical Subject Headings (MeSH) of the National Library of Medicine and their respective entry terms were shifted to the search fields to make the search more adequate and effective. The terms used for the search were: "temporomandibular disorder" AND "clinical trial", "temporomandibular disorder" AND "clinical trial", "electromyography" AND "temporomandibular disorder". Two independent reviewers verified the quality of the studies through a scored checklist, containing general items according to the PEDro and ROB-2 guidelines. Result: The search strategy enabled the retrieval of 5,000 articles using the previously determined keywords. After applying the eligibility criteria, 10 studies were included in this systematic review. Conclusion: The hypothesis that EMG can be used as a safe outcome measure to assess the post-treatment effects of TMD was not confirmed. The different methods of capturing, processing and analyzing the EMG signal were an important limiting factor for the comparative analysis of the results described in the studies selected for this review. All studies had different EMG capture and processing protocols. These methodological differences not only made data analysis difficult, but also indicated the need for standardization regarding the EMG signal capture, processing and analysis protocol.